Psychological Resilience and Social Support on Active Aging in Older Adults: An Empirical Study Based in Urban Communities in Guangdong - ZHANG, DEHUA (Pacific International Journal, 2026)
Objective: This study aims to explore the direct impact and interaction of psychological resilience and social support on active aging in older adults, and to examine the mediating effect of social support on the relationship between psychological resilience and active aging. Methods: A cross-sectional survey design was adopted. A questionnaire survey was conducted on 449 older adults aged 60 and above (mean age 71.5 ± 5.2 years) from Guangdong Province through random sampling. Descriptive statistics, correlation analysis, hierarchical regression analysis, and mediation effect tests were performed using SPSS 26.0 and PROCESS macro programs. Results :(1) Psychological resilience (r = 0.48, p < 0.001) and social support (r = 0.28, p < 0.001) were significantly positively correlated with active aging in older adults. (2) Hierarchical regression analysis showed that psychological resilience (β = 0.36, p < 0.001) and social support (β = 0.23, p < 0.001) independently and significantly positively predicted active aging. (3) Mediation analysis showed that social support partially mediated the relationship between psychological resilience and active aging, with a mediation effect value of 0.12, accounting for 25% of the total effect. Conclusion: This study indicates that high psychological resilience and strong social support are important protective factors for older adults to maintain active aging. Psychological resilience can not only directly enhance active aging but also indirectly play a role by strengthening the capacity for social support.